The forgiveness of blood - Heiblum, Leonardo 1970-; Lieberman, Jacobo 1970- (<<The>> Criterion Collection, 2012)
In northern Albania a teenage brother and sister are physically and emotionally trapped in a cycle of violence, a result of their father's entanglement with a rival clan over a piece of land
Original: USA, Albanien, Dänemark, Italien, Großbritannien 2011
director-approved DVD special edition features: new high-definition digital transfer, approved by director of photography Rob Hardy ; audio commentary by director and cowriter Joshua Marston ; two new programs: "Acting close to home", a discussion between the Marston and actors Refet Abazi, Tristan Halilaj, and Sindi Laçej, and "Truth on the ground", featuring new and on-set interwiews with producer Paul Mezey, Abazi, Halilaj, and Laçej ; audition and rehearsal footage ; audition and rehearsal footage ; trailer ; plus: a booklet featuring an essay by film critic Oscar Moralde
Bildformat 1.85:1 (16:9)
Keywords: Brothers and sisters / Albania / Drama; Vendetta / Albania / Drama; Clans / Albania / Drama; Jugend; Geschwister; Blutrache; Clan; Albanien; Film; DVD-Video